A novel approach to manufacture porous biocomposites using extrusion and injection moulding. (September 2016) - Etxabide, Alaitz; de la Caba, Koro; Guerrero, Pedro
Graphical abstract: Highlights: Gelatin sheets were successfully manufacture by extrusion. Gelatin biocomposites were moulded by injection. Porous microstructures were formed due to the cross-linking reaction. Porosity determined physico-chemical properties of biocomposites. Abstract: Gelatin biocomposites were successfully manufactured by extrusion followed by injection. The employment of these industrial techniques, which have not been widely used in the case of biopolymers such as gelatins, represents an important advance for the development of gelatin-based biocomposites. Furthermore, the use of a non-enzymatic reaction to cross-link proteins provides a new approach to improve and control some functional properties, such as solubility and swelling. The addition of lactose in the formulations, as well as the heating of injected biocomposites, caused gelatin cross-linking, changing the protein structure towards the formation of pores and thus, solubility, density, and swelling decreased. Additionally, the cross-linked biocomposites showed good mechanical properties.